Pemanfaatan Briket Arang Tempurung Kelapa sebagai Energi Alternatif - Muhammad Sahrul Firmansyah; Siti Fatimah Nurhayati (Universitas Muhammadiyah Surakarta, 2024)
Utilization of coconut shell waste as one of the raw materials for making charcoal briquettes is an innovative step in overcoming environmental and natural resource problems. This study aims to develop an effective and environmentally friendly method in converting coconut shells into charcoal briquettes that produce high quality. Briquettes made from coconut shells have a high calorific value among other biomass briquettes, namely 5780 cal / gr. The process of making charcoal briquettes begins with the collection of coconut shells as the main ingredient. Coconut shells are then processed through a series of stages, including drying, grinding, and mixing with additional materials as adhesives. This mixture is then pressed into briquette form using a briquette molding machine. From this study, the method of testing the manufacture of briquettes from coconut shells was carried out. Then in the collection of secondary data, it was done by comparing literature on relevant research. Making charcoal briquettes from coconut shells can have a positive impact economically and environmentally. In addition to reducing the amount of coconut shell waste that is disposed of, the use of charcoal briquettes can also support forest conservation efforts and reduce greenhouse gas emissions. With this method, it is expected to contribute positively to the management of natural resources and maintain environmental sustainability.